2009
DOI: 10.1080/00150190902873204
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-Sized Domain Structures in LuFeMO4(M= Cu, Co) Revealed by Energy-Filtered Transmission Electron Microscopy

Abstract: Diluted effect on the charge ordered (CO) structure in dielectric materials LuFeMO 4 (M = Cu, Co) were investigated by an energy-filtered transmission electron microscopy (TEM), in combination with a conventional TEM. It is revealed that partial substitution of Cu 2 + and Co 2 + for Fe 2 + in LuFe 2 O 4 destabilized the CO structure. In LuFeCuO 4 , there exist characteristic zigzag-shaped diffuse streaks and diffuse spots at the h/3-δ h/3-δ 0-type positions (h: integer, δ = 0.06) in reciprocal space, which ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It is known that Fe ions in LuFe 2 O 4 can be replaced by some ions to form LuFe M O 4 ( M = Mg, Mn, Cu, Zn) . In these systems, the formal valence of Fe ion is 3+, whereas that of M ions is 2+.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that Fe ions in LuFe 2 O 4 can be replaced by some ions to form LuFe M O 4 ( M = Mg, Mn, Cu, Zn) . In these systems, the formal valence of Fe ion is 3+, whereas that of M ions is 2+.…”
Section: Introductionmentioning
confidence: 99%
“…A previous article also reported that the dielectric constants become smaller in the order of R Fe 2 O 4 , R FeCoO 4 , R FeCuO 4 , and R GaCuO 4 ( R = Yb and Lu), which is ascribed to the suppression of charge transfer in the substituted systems. The Cu‐substituted system, LuFeCuO 4 , was reported to have a short‐ranged ordered structure in the triangular lattice . A recent work found that the number of oxygen vacancies plays an important role in the dielectric properties of LuFeCuO 4 , and the leakage current density decreases with oxygen annealing .…”
Section: Introductionmentioning
confidence: 99%
“…Such ordering was concluded from the zigzag diffuse pattern found in the TEM diffraction observation. This result indicates that the divalent and trivalent ions in the double triangular lattice form an ordering even in the crystal growth process [131][132][133][134]. As for LuCuGaO 4 , the neutron diffraction and the muon-spin relaxation experiment were performed [135].…”
Section: Development In Chemical Approachmentioning
confidence: 99%